Penggunaan MetodeProblem Based Learning Untuk Meningkatkan Keaktifan dan Hasil Belajar Arsitektur, klasifikasi penguat daya audio Peserta Didik SMKN 1 Adiwerna - Indriyanti (Universitas Pancasakti Tegal, 2020)
The research purposes to improve and definitive the increase in liveliness and learning result of students on basic architectural competencies, classification of audio power amplifier for students in class XI TAV 1 SMK N 1 Adiwerna Tegal even semester 2017/2018 school year. It was carried out in two circles by PBL (Problem Based Learning) method. The based on the research learning activity in the first cycle of students' learning activities was 50.78% and the second cycle was 80.87%. The learning result of cycle I were the percentage of the amount of students who had reached (fulfilling KKM) of 59.37%. In the second cycle the percentage of the total students who completed (has met KKM) amounted to 84.37%, which means that there has been an increase compared to the cycle I. Learning outcomes classically classified as complete (exceeding classical completeness) is 80%.